Gender and managerial competence: a comparison of male and female first-line nurse managers in Indonesia - Gunawan Joko; Aungsuroch Yupin; Fisher Mary L.; McDaniel Anna M. (Sciendo, 2021)
First-line nurse managers are more likely to work according to gender beliefs and stereotypes, which may affect their managerial competence. This study is aimed at comparing managerial competence of male and female first-line nurse managers in public hospitals in Indonesia.